Numerical analysis of energy savings due to the use of PCM integrated in lightweight building walls. Issue 1 (September 2020) - Sheeja, R.; Kumar, S.; Chandrasekar, P.; Jospher, Abraham J S; Krishnan, Sai
Abstract: A new type of PCM layer integrated into an exterior building wall is to reduce the amplitude of the indoor temperature and maintaining the better thermal comfort for human beings. A numerical simulation has been carried out with and without integration of PCM in building walls. In this paper, the effect of different configuration of external building walls were studied and analyzed by the integration of PCM building walls. Using finite difference method, one dimensional transient heat transfer model was developed and solved. The indoor temperature was also analyzed for the summer and winter climatic conditions of Chennai city, India (13.1 Latitude and 79.9 Longitude) in the PCM and Non-PCM buildings. The building wall consists of clay brick with filled with PCM. The numerical simulation result shows that, PCM filled with clay brick wall improves the thermal inertia significantly. Location of PCM layer in the building wall is one of the important factors to reduce the heat gain in the building wall before it enters the room.